2003
DOI: 10.2172/918286
|View full text |Cite
|
Sign up to set email alerts
|

Defect reduction in gallium nitride using cantilever epitaxy.

Abstract: Cantilever epitaxy (CE) has been developed to produce GaN on sapphire with low dislocation densities as needed for improved devices. The basic mechanism of seeding growth on sapphire mesas and lateral growth of cantilevers until they coalesce has been modified with an initial growth step at 950°C. This step produces a gable with ) 2 2 11 ( facets over the mesas, which turns threading dislocations from vertical to horizontal in order to reduce the local density above mesas. This technique has produced material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…All this information together indicated that the problem was with the initial growth of cantilevers and with the way they are grown together at coalescence. We found that two modifications to our CE growths were able to eliminate dark-block defects [9]. First, the initial nucleation of GaN on the mesas needed to be fully dense.…”
Section: Elimination Of Dark-block Defectsmentioning
confidence: 99%
“…All this information together indicated that the problem was with the initial growth of cantilevers and with the way they are grown together at coalescence. We found that two modifications to our CE growths were able to eliminate dark-block defects [9]. First, the initial nucleation of GaN on the mesas needed to be fully dense.…”
Section: Elimination Of Dark-block Defectsmentioning
confidence: 99%